AJSS 2019
DOI: 10.34091/ajss.12.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Impact of abusive supervision climate on employees’ prohibitive voice behavior through abusive supervision and cognitive rumination: A case of Pakistan

Abstract: The current paper focused on investigating the role an Abusive Supervision Climate (ASC) plays in Prohibitive Voice behavior of workers in Pakistani service industry. Sample from 330 pairs of supervisors and subordinates was collected from public sector banks, universities and hospitals. It was identified that social learning from the climate is a significant source of learned abusive behavior which leads to rumination and voice behavior in employees. Keywords: Abusive supervision climate, abusive supervision,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…More specifically, Kakkar et al (2016) suggests that employees opting for promotive voice gain support from their immediate supervisors, whereas, to avoid harmful practices, those employees may also prefer to raise prohibitive voice. In line with that, Tahir and Khan (2019) and Liang et al (2012) argue that employees engage in prohibitive voice to point out issues that may be harmful to organizational functioning. As prohibitive voice is risky and is mostly unwelcomed, and may be seen as destructive, employees sparingly engage in this form of voice (Lin and Johnson, 2015).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 90%
See 2 more Smart Citations
“…More specifically, Kakkar et al (2016) suggests that employees opting for promotive voice gain support from their immediate supervisors, whereas, to avoid harmful practices, those employees may also prefer to raise prohibitive voice. In line with that, Tahir and Khan (2019) and Liang et al (2012) argue that employees engage in prohibitive voice to point out issues that may be harmful to organizational functioning. As prohibitive voice is risky and is mostly unwelcomed, and may be seen as destructive, employees sparingly engage in this form of voice (Lin and Johnson, 2015).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 90%
“…Eissa et al (2019) and Tahir and Khan (2019) suggest that abusive supervision may be seen as a dysfunctional type of leadership where supervisors always consider their employees at fault, hence directing their anger and insults toward them. Abusive supervision leads to negative emotions such as distrust, annoyance and anxiety and ultimately, results in harmful behavior that is detrimental for organization (Eissa and Lester, 2017).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…When abusive supervision is perceived by most of the employees working in the same work environment, an abusive supervision climate occurs (Tahir & Khan, 2019). In an abusive supervision climate, the employees readjust their behaviours and attitudes (Khan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the same was not true for employee voice, and affective rumination did not lead to employees speaking up. However, a more recent study by Tahir and Khan (2019) showed that adverse work-related circumstances could activate work-related rumination and the consequential voice behaviour of employees. The study also acknowledged how this occurrence could be fostered by employees responding to the specific situation, utilising "intervention" means.…”
Section: Work-related Rumination and Employee Voice And Silencementioning
confidence: 99%